2011
DOI: 10.1111/j.1749-6632.2010.05931.x
|View full text |Cite
|
Sign up to set email alerts
|

The worldwide frozen embryo reservoir: methodologies to achieve optimal results

Abstract: Cryopreservation of the human embryo has been successfully achieved at the zygote (day 1), cleavage (day 2/3), and blastocyst (day 5) stages; however, each stage presents specific advantages and disadvantages. During the past decades, two major methods have been applied: slow freezing (equilibrium procedure) and vitrification (nonequilibrium procedure). The overwhelming majority of published data prove that the latest vitrification methods induce less cellular trauma and are a more effective cryopreservation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…1 Researchers were initially concerned with the effects of cryopreservation or cryostorage on the survival, development and molecular biology of the frozen embryo after thawing. 24 However, recent reports have demonstrated that cryostorage does not adversely affect post-thaw survival or pregnancy outcome during in vitro fertilization (IVF) or oocyte donation in patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 Researchers were initially concerned with the effects of cryopreservation or cryostorage on the survival, development and molecular biology of the frozen embryo after thawing. 24 However, recent reports have demonstrated that cryostorage does not adversely affect post-thaw survival or pregnancy outcome during in vitro fertilization (IVF) or oocyte donation in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Embryo cryopreservation has become an established procedure in the field of reproductive medicine [12, 30–32] accounting for a cumulative 28% of delivery rate following IVF programs at least in Europe [4, 10, 33]. Slow-freezing was the first technique of cryopreservation employed in IVF laboratories, but, in the last years, it has been progressively replaced by the method of vitrification of the basis of a quantity of literature recently reviewed reporting higher cryosurvival rate in both cleavage- and blastocyst-stage embyos [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that zona pellucida and mucin coat are essential for rabbit embryo development and implantation [28] and damage to zona pellucida is common phenomenon when embryos are cryopreserved in normal straws [44,30,58,20]. On the other hand, cryopreservation by ultra-rapid vitrification utilizing the MEV method and accelerated cooling/warming rates might avoid such damage [8]. Likewise, high recovery rates of the zona pellucida-intact pronuclear zygotes might also be attributed to the composition of vitrification media.…”
Section: Discussionmentioning
confidence: 99%